Дослідження динаміки горизонтальних рухів земної кори Європи за даними GNSS-спостережень (2000–2010 рр.) - Третяк, К. Р.; Вовк, А. І. (Видавництво Львівської політехніки, 2012)
Основна мета роботи – дослідження динаміки рухів земної кори Європи за період 2000–2010 рр . Визначено абсолютні та регіональні річні вектори швидкостей зміщень перманентних станцій і побудо-вано карти- схеми річних векторів швидкостей горизонтальних зміщень , виділено умовні блоки земної кори ( УБЗК), в межах яких спостерігається стала кінематика горизонтальних зміщень перманентних станцій. Визначено середню річну швидкість та напрям руху цих блоків . Отримані результати надалі будуть використані для вивчення деформації земної кори досліджуваного регіону. Основная цель работы – исследование динамики движений земной коры Европы за период 2000-2010 гг . Определены абсолютные и региональные годовые векторы скоростей смещений перманентных станций и построены карты-схемы годовых векторов скоростей смещения, выделены условные блоки земной коры (УБЗК), в пределах которых наблюдается постоянная кинематика горизонтальных смещений перманентных станций . Определены средние годовые скорости и направления движения этих блоков . Полученные результаты в дальнейшем будут использованы для изучения деформации земной коры исследуемого региона. The main aim of this work is the study of dynamics of crustal movements in Europe for the period from 2000 to 2010. Absolute and regional annual vect ors of velocity of displacement of permanent stations are estimated and schematic maps of annual rate of displacement vectors are created, conditional crustal blocks (CCB) which stable kinematics of horizontal displacements of permanent stations are selected. Average annual velocities and directions of movement of these blocks are estimated. These results will be further used to study the crustal deformation in surveying region.
Исследование динамики горизонтальных движений земной коры Европы по данным GNSS-наблюдений (2000–2010 гг.)
Study of dynamics of horizontal crustal movements in europe according to GNSS observation (2000–2010)
Keywords: Global Navigation Satellite System (GNSS); Global Positioning System (GPS); деформація; горизонтальна деформація; перманентна станція; умовний блок земної кори ( УБЗК); Global Navigation Satellite System (GNSS); Global Positioning System (GPS); деформация; горизонтальная деформация; перманентная станция; условный блок земной коры ( УБЗК); Global Navigation Satellite System (GNSS); Global Positioning System (GPS); deformation; horizontal deformation; a permanent station; conditional crustal block (CCB)